A clinical evaluation of prefabricated CAD-CAM crowns for restoring anterior and posterior primary teeth. Issue 3 (December 2020) - Hanafi, Louay; Altinawi, Mohamed
Abstract: Purpose: The purpose of this study was to produce an esthetic and economical prefabricated crowns which can be used as a final restoration for primary teeth by using CAD-CAM system. Methods: 44 children, five to nine year olds with at least one decayed primary teeth were included. This study was designed as a randomized controlled clinical trial, with 63 primary teeth were divided into two groups: CAD-CAM crowns (CCZC)[16 Posterior, 15 Anterior] and NuSmile crowns (NZC)[16 Posterior, 16 Anterior]. Crowns were evaluated at one-month, three-month, and six-month recall appointments, examining the following criteria: proximal contact area, marginal adaptation and Restoration failure. Maan-Whitney U, Friedman test and Wilcoxon tests were used for statistical analysis. Results: Analysis of variance showed poor marginal adaptation in all crowns, loss of proximal contact area in one mesial surface and two distal surfaces in posterior teeth which restored with CCZC compared to the two distal surfaces in posterior teeth with NZC. fracture occurred on the surface of one NZC after one month. However, there was no significant difference between NuSmile Crowns and CAD-CAM crowns after six months follow up (P > 0.05). Conclusions: Prefabricated CAD-CAM crowns are acceptable option as final restorations for primary teeth.